Pengaruh Work Life Balance & Reward System Terhadap Kepuasan Kerja Karyawan PT. Telkom Akses Kota Bengkulu - Marliza Ade Fitri; Yosi Olivia Riduan; Herwan Herwan (UNIVED Press, 2022)
This research is based on the importance of employee job satisfaction in achieving company goals. Factors that can affect employee job satisfaction include Work Life Balance & Reward System. The purpose of this study was to find out the effect of Work Life Balance and Reward System on employee job satisfaction PT. Telkom Access City of Bengkulu. This research uses a quantitative approach. Quantitative research methods are systematic, structured, and organized research from the beginning to the end of their research. The population in this study is an employee of PT. Telkom Access Bengkulu City and sampling using the Saturated Sample method